Coagulase-negative staphylococci (CoNS) as a significant etiological factor of laryngological infections: a review - Michał Michalik; Alfred Samet; Adrianna Podbielska-Kubera; Vincenzo Savini; Jacek Międzobrodzki; Maja Kosecka-Strojek (BMC, 2020)
Abstract This review article shows that coagulase-negative staphylococci (CoNS) are widely responsible for laryngological diseases. General characteristics of CoNS infections are shown in the introduction, and the pathogenicity in terms of virulence determinants, biofilm formation and genetic regulation mechanisms of these bacteria is presented in the first part of the paper to better display the virulence potential of staphylococci. The PubMed search keywords were as follows: CoNS and: nares infections, nasal polyps, rhinosinusitis, necrosing sinusitis, periprosthetic joint infection, pharyngitis, osteomyelitis of skull and neck bones, tonsillitis and recurrent tonsillitis. A list of laryngological infections and those related to skull and neck bones was presented with descriptions of the following diseases: rhinosinusitis, necrotizing sinusitis, nasal polyps, nares and nasal skin infections, periprosthetic joint infections, osteomyelitis, pharyngitis, and tonsillitis. Species identification and diagnostic problems challenging for diagnosticians are presented. Concluding remarks regarding the presence of CoNS in humans and their distribution, particularly under the effect of facilitating factors, are mentioned.